2014
DOI: 10.4028/www.scientific.net/kem.629-630.213
|View full text |Cite
|
Sign up to set email alerts
|

The Research of Influence on the Freezing Resistance and the Permeation Resistance of Concrete With Spraying Silane

Abstract: Silane, as an extremely hydrophobic material, changes concrete surface from hydrophilic state to hydrophobic state by spraying on the surface of concrete. It has the ability to block the external corrosive medium to improve the durability of concrete. Three types of strength grade of concrete (C30, C40, C50) were designed, after spraying with silane on the surface of concrete, to measure the penetration depth of silane and the influence on water-absorption rate, liquid-absorption rate, chloride ion diffusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The test results of Guo 14 showed that tetraethoxysilane could reduce the water absorption of concrete by 49.0%, the penetration depth of chloride ion by 28.5%, and the carbonation degree by 20%. Ge et al 15 pointed out that when silane was sprayed on the surface of concrete, the water absorption of concrete in 1 h decreased by more than 98%, the water absorption in 48 h decreased by more than 91%, the liquid absorption in 48 h (3% NaCl solution) decreased by more than 94%, the absorption and reduction rate of chloride ion decreased by more than 93%, the chloride ion diffusion coefficient decreased by 42%–48%, and the freeze–thaw resistance increased by five times. Wang et al 16 also found that compared with untreated concrete, the chloride diffusion coefficient of silane impregnated concrete was reduced by 37.4%.…”
Section: Introductionmentioning
confidence: 99%
“…The test results of Guo 14 showed that tetraethoxysilane could reduce the water absorption of concrete by 49.0%, the penetration depth of chloride ion by 28.5%, and the carbonation degree by 20%. Ge et al 15 pointed out that when silane was sprayed on the surface of concrete, the water absorption of concrete in 1 h decreased by more than 98%, the water absorption in 48 h decreased by more than 91%, the liquid absorption in 48 h (3% NaCl solution) decreased by more than 94%, the absorption and reduction rate of chloride ion decreased by more than 93%, the chloride ion diffusion coefficient decreased by 42%–48%, and the freeze–thaw resistance increased by five times. Wang et al 16 also found that compared with untreated concrete, the chloride diffusion coefficient of silane impregnated concrete was reduced by 37.4%.…”
Section: Introductionmentioning
confidence: 99%